M6A mRNA methylation controls autophagy and adipogenesis by targeting Atg5 and Atg7. Issue 7 (2nd July 2020) - Wang, Xinxia; Wu, Ruifan; Liu, Youhua; Zhao, Yuanling; Bi, Zhen; Yao, Yongxi; Liu, Qing; Shi, Hailing; Wang, Fengqin; Wang, Yizhen
ABSTRACT: N: 6 -methyladenosine (m 6 A), the most abundant internal modification on mRNAs in eukaryotes, play roles in adipogenesis. However, the underlying mechanism remains largely unclear. Here, we show that m 6 A plays a critical role in regulating macroautophagy/autophagy and adipogenesis through targeting Atg5 and Atg7 . Mechanistically, knockdown of FTO, a well-known m 6 A demethylase, decreased the expression of ATG5 and ATG7, leading to attenuation of autophagosome formation, thereby inhibiting autophagy and adipogenesis. We proved that FTO directly targeted Atg5 and Atg7 transcripts and mediated their expression in an m 6 A-dependent manner. Further study identified that Atg5 and Atg7 were the targets of YTHDF2 (YTH N6-methyladenosine RNA binding protein 2). Upon FTO silencing, Atg5 and Atg7 transcripts with higher m 6 A levels were captured by YTHDF2, which resulted in mRNA degradation and reduction of protein expression, thus alleviating autophagy and adipogenesis. Furthermore, we generated an adipose-selective fto knockout mouse and find that FTO deficiency decreased white fat mass and impairs ATG5- and ATG7-dependent autophagy in vivo . Together, these findings unveil the functional importance of the m 6 A methylation machinery in autophagy and adipogenesis regulation, which expands our understanding of such interplay that is essential for development of therapeutic strategies in the prevention and treatment of obesity. Abbreviations: 3-MA: 3-methyladenine; ACTB: actin, beta; ATG: autophagy-related; Baf A1: bafilomycin A1 ; CEBPA: CCAAT/enhancer binding protein (C/EBP), alpha; CEBPB: CCAAT/enhancer binding protein (C/EBP), beta; FABP4: fatty acid binding protein 4, adipocyte; FTO: fat mass and obesity associated; HFD: high-fat diet; LC-MS/MS: liquid chromatography-tandem mass spectrometry; MAP1LC3B/LC3: microtubule-associated protein 1 light chain 3 beta; m 6 A: N 6 -methyladenosine; MEFs: mouse embryo fibroblasts; MeRIP-qPCR: methylated RNA immunoprecipitation-qPCR; PPARG: peroxisome proliferator activated receptor gamma; RIP: RNA-immunoprecipitation; SAT: subcutaneous adipose tissue; siRNA: small interfering RNA; SQSTM1/p62: sequestosome 1; TEM: transmission electron microscopy; ULK1: unc-51 like kinase 1; VAT: visceral adipose tissue; WAT: white adipose tissue; YTHDF: YTH N6-methyladenosine RNA binding protein